Review Of The Intellectual Property Directorate General's Responsibility Regarding The Cancellation Of Well-Known Trademark Registration In The Same Class Of Goods - Laffaiza, Nasywa; Kansil, Christine S.T (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
The responsibility of the Directorate General of Intellectual Property (DJKI) in canceling the registration of famous trademarks in the same class of goods is an important issue in the protection of intellectual property rights in Indonesia. This study aims to analyze the authority of the Directorate General of Intellectual Property (DGIP) in canceling the registration of well-known trademarks that are deemed to harm the owners of well-known trademarks, especially when the newly registered trademark is in the same class of goods. This review examines the responsibilities and authorities of DJKI based on regulations governing trademark cancellation, such as Law No. 20 of 2016 on Trademarks and Geographical Indications, as well as decisions issued by DJKI related to trademark cancellation. This research also discusses the factors that influence DJKI's decisions in assessing whether a brand can be considered famous and whether the registration of a new brand can pose a risk of confusion in the market. The analysis results show that DJKI has a significant responsibility in maintaining the integrity of the trademark registration system and protecting the rights of famous trademark owners. This research provides recommendations on the importance of stricter supervision and law enforcement to ensure that famous brands are optimally protected from misuse and intellectual property rights violations in Indonesia